Progression to WHO criteria for antiretroviral therapy in a 7-year cohort of adult HIV-1 seroconverters in Abidjan, Côte d’Ivoire - Minga, Albert (World Health Organization, 2007)
OBJECTIVE: To estimate the probability of reaching the criteria for starting highly active antiretroviral therapy (HAART) in a prospective cohort of adult HIV-1 seroconverters in Abidjan, Côte d’Ivoire. METHODS: We recruited participants from HIV-positive donors at the blood bank of Abidjan for whom the delay since the estimated date of seroconversion (midpoint between last negative and first positive HIV-1 test) was ≤ 36 months. Participants were offered early trimethoprim-sulfamethoxazole (cotrimoxazole) prophylaxis, twice-yearly measurement of CD4 count and we made standardized records of morbidity. We used the Kaplan–Meier method to estimate the probability of reaching the criteria for starting HAART according to WHO 2006 guidelines. FINDINGS: 217 adults (77 women (35%)) were followed up during 668 person-years (PY). The most frequent diseases recorded were mild bacterial diseases (6.0 per 100 PY), malaria (3.6/100 PY), herpes zoster (3.4/100 PY), severe bacterial diseases (3.1/100 PY) and tuberculosis (2.1/100 PY). The probability of reaching the WHO 2006 criteria for HAART initiation was estimated at 0.09, 0.16, 0.24, 0.36 and 0.44 at 1, 2, 3, 4 and 5 years, respectively. CONCLUSION: Our data underline the incidence of the early HIV morbidity in an Ivorian adult population and provide support for HIV testing to be made more readily available and for early follow-up of HIV-infected adults in West Africa.